2020
DOI: 10.1007/s10741-020-09936-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral antidiabetic drugs and glucagon-like peptide-1 receptor agonists on left ventricular diastolic function in patients with type 2 diabetes mellitus: a systematic review and network meta-analysis

Abstract: The present study aimed to compare the effects of oral antidiabetic drugs (OADs) and glucagon-like peptide-1 receptor agonists (GLP-1RAs) on left ventricular diastolic function in patients with type 2 diabetes mellitus using a network meta-analysis of randomized controlled trials (RCTs). Literature searches were conducted on Medline, the Cochrane Controlled Trials Registry, and ClinicalTrials.gov. RCTs that assessed the effects on left ventricular diastolic function of OADs and GLP-1RAs in patients with type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Both parameters are relevant for diabetic cardiomyopathy and HFpEF (100). In addition, a systematic review comparing the effect of GLP-1 agonists to different antidiabetics on LV diastolic function has concluded that liraglutide monotherapy offers a considerably beneficial outcome (101). Interestingly, the EAT was found to express GLP-1 receptors in contrast to subcutaneous fat in the same patient (102).…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%
“…Both parameters are relevant for diabetic cardiomyopathy and HFpEF (100). In addition, a systematic review comparing the effect of GLP-1 agonists to different antidiabetics on LV diastolic function has concluded that liraglutide monotherapy offers a considerably beneficial outcome (101). Interestingly, the EAT was found to express GLP-1 receptors in contrast to subcutaneous fat in the same patient (102).…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%
“…Among these, a study with liraglutide demonstrated a reduction in LV filling pressure and an improvement in diastolic function, both parameters relevant for progression of diabetic cardiomyopathy and symptomatic HFpEF [171]. This result was confirmed by a systematic review [172]. Other experimental studies support an effect of fat mass reduction of GLP-1 RAs by increasing insulin sensitivity, lipolysis, and energy expenditure.…”
Section: Incretin-based Therapymentioning
confidence: 69%
“…The absence of RCTs that met pooling criteria precluded planned meta-analyses. Previously published indirect net-work metaanalyses focused on intermediate outcomes of diastolic dysfunction regardless of baseline HFpEF and did not find consistent superiority of SGLT2 inhibitors when compared with placebo or other anti-diabetic medications [74,75] . Previously published direct meta-analysis concluded that SGLT2 inhibitors reduced the risk of cardiovascular death or heart-failure hospitalization regardless of baseline heart failure diagnosis [15] .…”
Section: Discussionmentioning
confidence: 95%
“…We found no studies that reported adverse effects from SGLT2 inhibitors specifically in adults with HFpEF [73] . Limited evidence of some improvement in intermediate outcomes of diastolic dysfunction lack clinical significance with valid prediction of better patient-centered outcomes and healthcare utilization required in future studies [74,75] . The absence of RCTs that met pooling criteria precluded planned meta-analyses.…”
Section: Discussionmentioning
confidence: 99%